2021
DOI: 10.3389/fpsyt.2021.758105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Type and Frequency of Social Participation on Depressive Symptoms Among Older Chinese Adults: Is There a Gender Difference?

Abstract: Objectives: Social participation may prevent depressive symptoms in older adults. But research to date ignores gender differences in the associations between social participation and depressive symptoms. The purpose of this study was to determine the effect of different type and frequency of social participation on depressive symptoms, as well as if there is a gender difference in these correlations among older Chinese adults.Methods: Data was obtained from adults aged 60 years or above in the 2018 China Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…In addition, interests and life experiences usually differ along certain lines for males and females [ 20 ]. These findings were in accordance with the results of other studies such as those by Li et al and Xiao et al, which indicated that females tended to participate more in housework and light-intensity activities than males, who appeared to be more engaged outside the home, including participation in sports and socially oriented activities, in China [ 15 , 19 ]. These phenomena seem to hold true in both Eastern and Western cultures [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, interests and life experiences usually differ along certain lines for males and females [ 20 ]. These findings were in accordance with the results of other studies such as those by Li et al and Xiao et al, which indicated that females tended to participate more in housework and light-intensity activities than males, who appeared to be more engaged outside the home, including participation in sports and socially oriented activities, in China [ 15 , 19 ]. These phenomena seem to hold true in both Eastern and Western cultures [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have pointed out that social participation could reduce individuals’ negative emotional experiences (e.g., depressive symptoms) [ 11 ] and enhance their well-being [ 12 , 13 ]. A study of 314 healthy adults demonstrated that individuals involved in volunteering or paid work reported higher levels of well-being [ 14 ]; social and community-related activities could promote better emotional health [ 15 ]. However, social activities are so varied that it is difficult to cover them comprehensively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CHARLS database, the disability status was assessed with the question “Do you have one of the following [physical disabilities, brain damage/mental retardation, vision problem, hearing problem, speech impediment] disabilities?” Responses were categorized as “yes” or “no” ( 25 ). Participants with two or more types of disabilities were defined as multiple disabilities ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…These findings may imply that retirement could represent a trigger risk factor in those individuals presenting with psychiatric vulnerability or a previous attenuated form of mood disorder. On the other hand, ( 9 ) investigated prevention strategies in Chinese individuals aged ≥65 years old. The sample, balanced for gender, included 6,287 elderly adults.…”
mentioning
confidence: 99%